Photodynamic Therapy Combined with Liquid Nitrogen Cryotherapy and Curettage for the Treatment of Recalcitrant Periungual and Subungual Warts: Clinical Experience and Literature Review - Kuixia Xie; Meihong Cheng; Bo He; Wei Li; Wenying Zhong (Indian Journal of Dermatology)
Warts are caused by human papillomavirus (HPV) infection and can involve multiple parts of skin and mucosa, of which periungual and subungual warts are the most difficult to treat. Periungual or subungual wart is verruca vulgaris growing around or under the fingernail, destroying and deforming the nail and nail bed. Currently, liquid nitrogen cryotherapy and CO2 laser are often used for the treatment. Clinically, few doctors routinely use photodynamic therapy (PDT) to treat viral warts. We used PDT combined with liquid nitrogen cryotherapy and curettage to successfully treat a case of intractable periungual and subungual warts.